Regulatory Effect of Connexin 43 on Basal Ca2+ Signaling in Rat Ventricular Myocytes - Li, Chen; Meng, Qingli; Yu, Xinfeng; Jing, Xian; Xu, Pingxiang; Luo, Dali (PLOS ONE, 2012)
Background It has been found that gap junction-associated intracellular Ca2+ [Ca2+]i disturbance contributes to the arrhythmogenesis and hyperconstriction in diseased heart. However, whether functional gaps are also involved in the regulation of normal Ca2+ signaling, in particular the basal [Ca2+]i activities, is unclear. Methods and Results Global and local Ca2+ signaling and gap permeability were monitored in cultured neonatal rat ventricular myocytes (NRVMs) and freshly isolated mouse ventricular myocytes by Fluo4/AM and Lucifer yellow (LY), respectively. The results showed that inhibition of gap communication by heptanol, Gap 27 and flufenamic acid or interference of connexin 43 (Cx43) with siRNA led to a significant suppression of LY uptake and, importantly, attenuations of global Ca2+ transients and local Ca2+ sparks in monolayer NRVMs and Ca2+ sparks in adult ventricular myocytes. In contrast, overexpression of rat-Cx43 in NRVMs induced enhancements in the above measurements, and so did in HEK293 cells expressing rat Cx43. Additionally, membrane-permeable inositol 1,4,5-trisphosphate (IP3 butyryloxymethyl ester) and phenylephrine, an agonist of adrenergic receptor, could relieve the inhibited Ca2+ signal and LY uptake by gap uncouplers, whereas blockade of IP3 receptor with xestospongin C or 2-aminoethoxydiphenylborate mimicked the effects of gap inhibitors. More importantly, all these gap-associated effects on Ca2+ signaling were also found in single NRVMs that only have hemichannels instead of gap junctions. Further immunostaining/immunoblotting single myocytes with antibody against Cx43 demonstrated apparent increases in membrane labeling of Cx43 and non-junctional Cx43 in overexpressed cells, suggesting functional hemichannels exist and also contribute to the Ca2+ signaling regulation in cardiomyocytes. Conclusions These data demonstrate that Cx43-associated gap coupling plays a role in the regulation of resting Ca2+ signaling in normal ventricular myocytes, in which IP3/IP3 receptor coupling is involved. This finding may provide a novel regulatory pathway for mediation of spontaneous global and local Ca2+ activities in cardiomyocytes.